2018
DOI: 10.1111/pce.13131
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic and salicylic acid response in the fern Azolla filiculoides and its cyanobiont

Abstract: Plants sense and respond to microbes utilizing a multilayered signalling cascade. In seed plants, the phytohormones jasmonic and salicylic acid (JA and SA) are key denominators of how plants respond to certain microbes. Their interplay is especially well-known for tipping the scales in plants' strategies of dealing with phytopathogens. In non-angiosperm lineages, the interplay is less well understood, but current data indicate that it is intertwined to a lesser extent and the canonical JA/SA antagonism appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 194 publications
0
30
0
2
Order By: Relevance
“…However, other lycophytes including another species from the genus Selaginella did not produce measurable levels of JA [127], supporting the notion of a high species-specificity in JA biosynthesis. Similarly, some species of ferns show pronounced JA responses, while others do not [134-136]; likewise, the production of JA was shown to be species-specific in ferns [127]. This distribution of JA biosynthesis becomes less patchy in gymnosperms and angiosperms, as shown in the dataset by Gachet and colleagues [127], where only one species in each of these two lineages was identified that did not produce a detectable amount of JA.…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 98%
See 1 more Smart Citation
“…However, other lycophytes including another species from the genus Selaginella did not produce measurable levels of JA [127], supporting the notion of a high species-specificity in JA biosynthesis. Similarly, some species of ferns show pronounced JA responses, while others do not [134-136]; likewise, the production of JA was shown to be species-specific in ferns [127]. This distribution of JA biosynthesis becomes less patchy in gymnosperms and angiosperms, as shown in the dataset by Gachet and colleagues [127], where only one species in each of these two lineages was identified that did not produce a detectable amount of JA.…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 98%
“…Indeed, Thaler et al [141] and Han [125] suggested that the JA/SA-antagonism arose at the earliest in seed plants. Along these lines, it was hypothesized that in the fern Azolla some JA-orchestrated signaling responses may be initiated via SA instead of JA because MeSA application induced the expression of Plant Defensin 1.4 ( AfPDF1.4 [136]); in Arabidopsis, PDFs are JA-responsive [142]. These results, together with the data from mosses, speak in favor of a reduced antagonism – or perhaps complete lack thereof – between JA and SA in mosses and ferns.…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
“…There are two possible explanations for this outcome: (1) JA is not involved in anti-herbivore responses in all ferns, (2) all ferns use JA but differ in their thresholds or the time needed to trigger anti-herbivore-responses. Recent studies indicate that the water fern Azolla filiculoides has genes for the production and sensing of jasmonic and salicylic acids, indicating that JA signalling can be a highly conservative mechanism (de Vries et al 2018). More studies are needed to establish if JA is a universal molecule mediating anti-herbivore responses in plants, and if so, the threshold levels and response times required by different fern species.…”
Section: Discussionmentioning
confidence: 99%
“…Відомо лише, що екзогенне використання СК при культивуванні водної папороті Azolla filiculoides Lam., яка утворює симбіоз з азотфіксуючою ціанобактерією Trichormus azollae (Strasburger) Komárek & Anagnostidis (Nostoc azollae), виявило присутність у папороті СК-генів, відповідальних за експресію та сигналінг. Крім того, екзогенна СК впливала на активність генів ціанобіонта (De Vries et al, 2018).…”
Section: вступunclassified